Recurring Bullies - Matthew Jackson; Ehud Kalai (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
In a recurring game, a stage game is played consecutively by different groups of players, with each group receiving information about the play of earlier groups. Starting with uncertainty about the distribution of types in the population, late groups may learn to play a correct Bayesian equilibrium, as if they know the type distribution. This paper concentrates on Selten's Chain Store game and the Kreps, Milgrom, Roberts, Wilson phenomenon, where a small perceived inaccuracy about the type distribution can drastically alter the equilibrium behavior. It presents sufficient conditions that prevent this phenomenon from persisting in a recurring setting.
Keywords: 330